Exploration of Indigenous Fungi: Identification of Fungal Isolates from Industrial Waste Disposal Rivers - Dewi Ratna Stia; Sanjayasari Dyahruri; Palupi Endah Sri; Kurniawati Any; Ramadani Putri; Nida Arroyan Yasinta (E3S Web of Conferences)
This research focuses on exploring indigenous fungi from industrial waste discharged into rivers. Sampling was conducted in the Ciliwung and Krukut rivers at several points in the waste disposal environment. The purpose of this study was to identify the presence of fungi that have the potential to degrade industrial waste components from the waste-polluted climate itself. The method includes isolating fungi by dilution from sediment and water samples, which are grown using potato dextrose agar (PDA) media. After the isolation, characterisation was done to identify the fungus types found. The results of this study showed the presence of 5 fungal isolates that have great potential in degrading industrial waste. These findings suggest that local fungi from Jakarta landfills could potentially be used for bioremediation as a solution to reduce the impact of hazardous waste on the environment. Waste management using fungi supports the achievement of SDG 6 (clean water and sanitation) by improving water quality through the degradation of harmful compounds, SDG 12 (responsible consumption and production) by providing sustainable waste management methods, and SDG 14 (marine ecosystems) by prevent river pollutants from reaching the sea to maintain the health of the aquatic ecosystem.